Development of a Computer-generated Digital Patient for Teaching and Assessment in Pharmacy : Final Report. - Newby, David; Jin, Jesse; Summons, Peter; Athauda, Rukshan; Park, Mira; Schneider, Jennifer; Kable, Sheree; Marriott, Jennifer; Duncan, Gregory; Simpson, Maree; Xu, Richard (Australian Learning and Teaching Council, 2011)
Communication skills are essential for pharmacists as they must get a good oral history to manage minor illnesses. Much time is devoted to these skills in pharmacy courses, but there are limited opportunities for students to practice and get feedback. This is the final report from a project that developed a computer-generated virtual patient for students to practice communication, diagnostic and clinical skills in managing minor illnesses. The software uses a realistic three-dimensional model 'patient' to which students 'ask' questions of, and the 'patient' responds. It captures the questions and responses, the chosen diagnosis and management, providing feedback on which questions were asked, which they should have been asked, and the correct diagnosis and treatment for the condition. The software was tested using 67 pharmacy students at three universities. Students felt the software helped them learn what questions to ask, and they liked the feedback they received. There were trends toward greater confidence in communications skills, and asking more generic questions (eg 'are you pregnant') after using the software. International students were less positive, and scored worse on their confidence and question asking compared to domestic students, owing largely to language difficulties. Results suggest the software may have a role early in pharmacy programs.